2013
DOI: 10.1111/echo.12200
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Functional Remodeling in Lone Atrial Fibrillation: A Two‐Dimensional Speckle Tracking Echocardiographic Study

Abstract: Remodeling of LA booster pump, reservoir, and conduit function in LAF patients can be detected by 2DSTE before structural remodeling. Occurrence of LAF is associated with impairment of LA intrinsic myocardial properties. LASa can differentiate LAF patients and lower LASa is associated with early recurrence of AF after ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…This notion is supported by another recent report in which global LA strain at late diastole was shown to be a predictor of early AF recurrence after catheter ablation. 15 It should be noted that LA volume was not a statistically significant predictor of AF recurrence after catheter ablation in either study, suggesting that functional LA remodeling may be more sensitive than structural LA remodeling in predicting the outcome of AF ablation.…”
Section: Article P 1695mentioning
confidence: 63%
“…This notion is supported by another recent report in which global LA strain at late diastole was shown to be a predictor of early AF recurrence after catheter ablation. 15 It should be noted that LA volume was not a statistically significant predictor of AF recurrence after catheter ablation in either study, suggesting that functional LA remodeling may be more sensitive than structural LA remodeling in predicting the outcome of AF ablation.…”
Section: Article P 1695mentioning
confidence: 63%
“…Previous reports have shown that some disease (hypertension, atrial fibrillation, coronary artery disease, etc.) may lead to left atrial phasic dysfunction evaluated by 2D-STE [22, 23]. Additionally, the longitudinal strain and strain rate, which are inversely related to LA wall fibrosis, have been reported to be a feasible and reproducible method to assess LA myocardial function [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…STE analysis has been demonstrated to be a feasible method to assess global and phasic LA longitudinal strains and strain rates in healthy subjects and in patients with LA dysfunction. [16][17][18][19] SRs has been used as an index of LA reservoir function, 27 while SRe and SRa are accepted as indices of LA conduit and LA contractile function, respectively. 9,28,30 In our study, both global and segmental systolic strains were all significantly reduced in the SLE group (all p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The feasibility and reproducibility of STE for LA mechanics have been recently validated. [16][17][18][19] The aims of the present study were: (1) to evaluate LA function and volume by STE-derived strain and strain rate in SLE patients compared to controls, (2) to assess the relationship of LA function and varying grades of LVDD in SLE patients and (3) to investigate effects of some major risk factors on LA function in SLE patients.…”
Section: Introductionmentioning
confidence: 99%